2016
DOI: 10.1111/desc.12446
|View full text |Cite
|
Sign up to set email alerts
|

The influence of bilingualism on the preference for the mouth region of dynamic faces

Abstract: Bilingual infants show an extended period of looking at the mouth of talking faces, which provides them with additional articulatory cues that can be used to boost the challenging situation of learning two languages (Pons, Bosch & Lewkowicz, 2015). However, the eye region also provides fundamental cues for emotion perception and recognition, as well as communication. Here, we explored whether the adaptations resulting from learning two languages are specific to linguistic content or if they also influence the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
51
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 35 publications
10
51
1
Order By: Relevance
“…At 4 and 12 months of age, infants growing up in a bilingual environment pay more attention to the mouth region than their monolingual peers (Pons, Bosch, & Lewkowicz, ). The same pattern of results is observed at 8 months when presenting bilingual and monolingual infants with nontalking communicative faces (Ayneto & Sebastian‐Galles, ). Taking into account that in daily face‐to‐face situations, communicative faces usually speak, both of these results suggest that bilingual infants might have developed this increased preference for the mouth region of communicative faces as an adaptive mechanism to overcome the challenge of learning two languages at the same time (for reviews, see Costa & Sebastián‐Gallés, ; Werker, ).…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…At 4 and 12 months of age, infants growing up in a bilingual environment pay more attention to the mouth region than their monolingual peers (Pons, Bosch, & Lewkowicz, ). The same pattern of results is observed at 8 months when presenting bilingual and monolingual infants with nontalking communicative faces (Ayneto & Sebastian‐Galles, ). Taking into account that in daily face‐to‐face situations, communicative faces usually speak, both of these results suggest that bilingual infants might have developed this increased preference for the mouth region of communicative faces as an adaptive mechanism to overcome the challenge of learning two languages at the same time (for reviews, see Costa & Sebastián‐Gallés, ; Werker, ).…”
Section: Introductionsupporting
confidence: 71%
“…Previous findings by Pons et al. () and Ayneto‐Gimeno & Sebastian‐Galles () have shown that during their first year of life, bilingual infants look more at the mouth region of talking and nontalking faces than their monolingual peers. Here we found the same pattern of results at a later stage of development but we also went one step further: We showed that during their second year of life (15 months of age), bilingual infants kept looking at the mouth region of the speaker rather than disengaging from it, preventing them from anticipating the appearance of additional information coming from the eyes region (EB movement).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Mouth movement provides more relevant linguistic information than does information from the eyes, and in the first year, infants raised with more than one language attend to the more informative source. A recent study by Ayneto and Sebastian-Galles (in press) showed that this bias for focusing on the mouth by bilingual children extends beyond linguistic information and also characterized attention to adult faces displaying emotional states; 8-month old bilingual infants focused on the mouth more than monolingual infants but by 12 months this difference was no longer found.…”
Section: Evidence For Bilingual Effects On Cognitionmentioning
confidence: 99%
“…Toward the latter half of the first year, infants begin to attend more to the mouth than to the eyes (Tenenbaum, Shah, Sobel, Malle, & Morgan, 2013). A recent study by Tsang, Atagi, and Johnson (2018) confirmed a relation between attention to talking mouths and increasing verbal skills for both monolingual and bilingual infants between 6 and 12 months old, but the shift of attention from the eyes to the mouth was found earlier for infants exposed to bilingual environments than for those in monolingual environments (Ayneto & Sebastián-Gallés, 2017). A recent study by Tsang, Atagi, and Johnson (2018) confirmed a relation between attention to talking mouths and increasing verbal skills for both monolingual and bilingual infants between 6 and 12 months old, but the shift of attention from the eyes to the mouth was found earlier for infants exposed to bilingual environments than for those in monolingual environments (Ayneto & Sebastián-Gallés, 2017).…”
mentioning
confidence: 95%